SOCIAL SITUATION AND PROBLEMS OF THE RURAL POPULATION IN THE 60-80S OF THE 20TH CENTURY - Ollomuradov Nurali (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article analyzes the changes and problems related to the social life of the rural population of the southern regions of Uzbekistan in the 60s-80s of the 20th century on the basis of concrete evidence